Leis de escala em mapeamentos discretos - Teixeira, Rivania Maria do Nascimento (2016)
In this work we are going to investigate the scale formalism in discret mappings. In 1D mappings, we explore the asymptotic decays to the steady state with focus in three types of bifurcation: transcriptical, pitchfork and period-doubling. We identify this behavior through a well defined generalized homogeneous function with critical exponents. Next to the bifurcation point, the decay to the fix point occurs by an exponential function, which is given by a power law that is independent of the non-linearity mapping. The numerical results obtained agree with the analytical results. We also apply the scale formalism in conservatives and dissipatives bidimensional mappings. In the conservative case, our goal was analyze the behavior of the chaotics orbits next to the phase transition from the integrable to the non-integrable. Next to that transition, we describe the dynamical system using a generalized homogeneous function for which we found a power law that describe the behavior of the criticality. Through a phenomenological discussion, we found critical exponents in agree with the analytical description. In the dissipative case, our main goal was to investigate the influence of a dissipative term in the dynamics, causing a phase transition - suppression of unlimited difusion of the action variable. Following a phenomenological approach with an analytical description, we were able to determine the critical exponents using a generalized homogeneous function.